1985
DOI: 10.1139/b85-341
|View full text |Cite
|
Sign up to set email alerts
|

Rachis vascularization and leaflet venation in developing leaves of Fraxinus pennsylvanica

Abstract: LARSON, P. R. 198.5. Rachis vascularization and leaflet venation in devclopiny leaves of Frcrsinu.spenn.sy/vnnica. Can. J . Bot. 63: 2383-2392. Leaves of Fraxi~l~i.spent~.sylvnt~ica are sewcd by a double tracc that exits thc stcm vasculature through a single gap. During embryonic leaf dcvclopment, the leaf traces subdivide in the nodc to produce subsidiary bundlcs that differentiate acropetally in the leaf base and basipetally in the stem. The acropetal bundles converge distally in the node to form a rachis va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In studies with cottonwood {Populus deboides), we have demonstrated the efficacy of "C in verifying functional transport pathways (Larson et al 1972, Larson andDickson 1973) previously mapped by anatomical analyses (Larson 1975, Isebrands and Larson 1977a,b, 1980. Cottonwood leaves are served by a central trace (C) plus right (R) and left (L) lateral traces that enter the node independently from the stem cylinder.…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…In studies with cottonwood {Populus deboides), we have demonstrated the efficacy of "C in verifying functional transport pathways (Larson et al 1972, Larson andDickson 1973) previously mapped by anatomical analyses (Larson 1975, Isebrands and Larson 1977a,b, 1980. Cottonwood leaves are served by a central trace (C) plus right (R) and left (L) lateral traces that enter the node independently from the stem cylinder.…”
mentioning
confidence: 52%
“…For example, in green ash with a plastochron of about 4.5 days, the transition is more abrupt and occurs closer to the apex than in honeylocust with a plastochron of about 2.5 days. In marked contrast, the transition in cottonwood, with a plastochron of 1-1-day, is more gradual and occurs well down from the apex (Larson 1977).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations